Utilities of Botulinum Toxins in Dermatology and Cosmetology - Naik PP (Dove Medical Press, 2021)
Piyu Parth Naik Department of Dermatology, Saudi German Hospital and Clinic, Dubai, United Arab EmiratesCorrespondence: Piyu Parth NaikDepartment of Dermatology, Saudi German Hospital and Clinic, Opposite Burj Al Arab, Dubai, United Arab EmiratesTel +971 503725616Email drpiyu85@gmail.comAbstract: Botulinum toxin (BoNT) is a neurotoxin produced by the Clostridium botulinum bacterium with a well-known efficacy and safety profile in the focal idiopathic hyperhidrosis treatment. BoNT comprises seven different neurotoxins; however, only toxins A and B are clinically employed. BoNT is lately practiced in off-label therapies for a variety of skin diseases. Scar prevention, hyperhidrosis, rhytides, eccrine nevus, alopecia, psoriasis, Darier disease, bullous skin disease, pompholyx and Raynaud's phenomenon are some of the novel indications for BoNT in cosmetic and notably non-cosmetic aspects of dermatology. To employ BoNT correctly in clinical practice, we must have a thorough understanding of the functional anatomy of the mimetic muscles. An intensive literature search was conducted to update all dermatology-oriented experiments and clinical trials on the described element of BoNT for this general overview of BoNT use in dermatology. This review aims to analyse the role of BoNT in dermatology and cosmetology.Keywords: botulinum toxin, BoNT, Clostridium botulinum, dermatology, cosmetology, neurotoxin